PSYCHOLOGICAL EMPOWERMENT, SELF LEADERSHIP, CORE SELF EVALUATION, WORK AS A CALLING AMONG ENTREPRENEURS - Narula, Aashna (Digital Repository of Theses, 2023)
Entrepreneurship has rekindled the interest of a growing body of psychology-based researchers. The field is developing and getting more attention. Psychological empowerment is a motivational construct that involves feeling competent, having an impact, feeling meaningful and having autonomy in one’s work. Self-leadership is the process of influencing oneself to achieve personal goals and lead oneself in positive direction. Core self-evaluation is a personality trait that encompasses an individual’s self- esteem, locus of control, emotional stability, and self-efficacy. Work as a Calling is a belief that one’s work is fulfilling and meaningful vocation that contributes to a greater purpose. The proposed investigation aims to explore correlates & predictors of Psychological Empowerment, Self-Leadership, Core Self Evaluation & Work as a Calling among male & female entrepreneurs. A total sample of 200 entrepreneurs (100 Males & 100 Females) was collected from Indian cities in the age 25 to 50 years. Standardized scales were used to measure psychological empowerment, self-leadership, core self-evaluation and work as a calling among entrepreneurs. The results found out significant relationship among psychological empowerment, self-leadership, core self-evaluation and work as a calling among entrepreneurs. Female entrepreneurs were found to be higher on self-talk as compared to male entrepreneurs. Further, subdimenisons of psychological empowerment and self leadership were retained as signifcant predictors of Core Self Evaluation. As a result, the proposed research aimed in improving the noted psychological factors that affect entrepreneurs. By fostering psychological empowerment, self-leadership, positive core self-evaluations, and a sense of work as a vocation, entrepreneurs can cultivate the resiliency, determination, and passion necessary to create successful and sustainable businesses. Implementation of mentoring programmes, training, and other forms of assistance designed to enhance these factors and, ultimately, entrepreneurial outcomes, are important.